Penguatan Daya Saing UMKM Fashion Batik 'Dejarumi' Melalui Optimalisasi Platform Online dan Inovasi Produk - Muhammad Eka Purbaya; Silvia Van Marsally; Syarif Hidayatuloh; Muhammad Faris Hilmy (Jurnal Pengabdian Masyarakat Akademisi, 2026)
Digitalization and modernization of production equipment are crucial factors in increasing the competitiveness of MSMEs in the fashion sector. However, Dejarumi MSME in Banyumas Regency, which promotes inclusive batik by empowering workers with disabilities, faces obstacles such as low production capacity and limited digital market reach. This community service program aims to strengthen Dejarumi's business ecosystem through an upstream-to-downstream transformation strategy. The implementation methods included modernizing production equipment (high-speed sewing machines, fabric cutting machines, and steam irons), developing a transactional e-commerce website, and optimizing marketing via Instagram and TikTok. The results showed a 16.32% increase in production time efficiency, with the manufacturing time per unit decreasing from 340 minutes to 284.5 minutes. Weekly production capacity also rose by 19.66%. On the marketing side, social media optimization successfully reached over 15,000 cumulative views and generated direct sales conversions. The use of digital platforms and modern production tools not only improved business performance but also established operational independence for workers with disabilities. Overall, this program has successfully created a more competitive, professional, and inclusive batik business model in the national market.